Liquid fuel synthesis in microreactors - Hafeez, Sanaa; Manos, George; Al-Salem, S. M.; Aristodemou, Elsa; Constantinou, Achilleas (My University, 2018)
The demand for energy is continuously increasing worldwide. This places a constant strain on the production and availability of fossil fuels on which most current energy sources are based. Thus, alternative sources of energy (non-fossil based) are urgently needed to produce liquid fuels. However, conventional technologies and reactors used for these alternative processes have been associated with low mass and heat transfer rates, long reaction times and extreme temperatures and pressures. To address these limitations, microreactors have been developed and utilised over the past decade, and have been proven to increase product yields and reduce residence time and product selectivity when compared to conventional reactors. This paper provides an in-depth review of the liquid fuel production routes over the last decade, and highlights the advantages of microreactors that have been successfully employed to overcome some of the issues faced with conventional bulk reactors.